Analisis Implementasi Pengawasan Ekspor Impor Barang Pada KPPBC Tipe Madya Pabean Belawan - Mahani Faiza Aulia; Juliana Nasution (LPPM Universitas Labuhanbatu, 2021)
KPPBC Tipe Madya Pabean Belawan is one of the vertical units Direktora Jendral Bea dan Cukai ministry of the republic Indonesia, which oversees the work area covering the port of Belawan which is one of the major sea ports in Indonesia. This study aims to determine the implementation of the export import supervision of goods at the KPPBC Tipe Madya Pabean Belawan. Primary data is in the form of direct interviews with information service center staff anf prosecution and investigation staff. Secondary data in the form of company documentation, web and internet. The results of this study conclude thet the implementation of the export import supervision of goods at the KPPBC Tipe Madya Pabean Belawan has been going well and in accordance with customs regulations, but there are inhibiting and supporting factors in the export import supervision. The inhibiting factor is the limited human resources with awide enough working area so that it is not possible to carry out comprehensive supervision at the same time and the lack of knowledge of new service users regarding the provisions of customs regulations. Supporting factor for the supervision of exports and imports are eduquate facilities and infrastructure and the importers who do import activities are familiar with customs regulation, makin it easier for the supervisory unit to supervise exported and imported goods.